Cardiovascular complications in chronic active Epstein–Barr virus disease: a case report and literature review - Feng, Zhiyuan; Duan, Hongyu; Wang, Lin; Yu, Huan; Zhou, Kaiyu; Hua, Yimin; Wang, Chuan; Liu, Xiaoliang (Frontiers in Pediatrics, 2025)
BackgroundCardiovascular involvement is a rare but severe complication of Epstein–Barr virus (EBV) infections. Patients with chronic active EBV (CAEBV) are at increased risk of developing cardiovascular complications and have a poor prognosis. Here, we report the rare case of a pediatric patient with CAEBV and EBV- hemophagocytic lymphohistiocytosis (HLH) complicated with a giant coronary artery aneurysm (CAA) and thrombosis, a giant Valsalva sinus aneurysm, and ascending aorta dilation seven years after the disease onset.Case presentationA previously healthy 3-year-old girl was initially misdiagnosed as presenting incomplete Kawasaki disease complicated by coronary artery lesions (CALs) for which she received intravenous immunoglobulin and aspirin therapy. Subsequently, she was transferred to our hospital, where we diagnosed her as having a primary EBV infection. After acyclovir therapy, her clinical symptoms resolved with negative EBV-DNA, and she was discharged home with aspirin treatment for the remaining CALs. However, she did not have regular follow-ups after that. Seven years later, the 10-year-old girl developed a prolonged fever and fatigue, and she was diagnosed as presenting CAEBV and EBV-associated hemophagocytic lymphohistiocytosis (EBV-HLH) due to the presence of a high EBV-DNA load, prolonged fever, splenomegaly, bicytopenia, hypertriglyceridemia, hypofibrinogenemia, hemophagocytosis, low NK-cell activity, and increased levels of ferritin and soluble CD25. The echocardiography images showed giant left and right coronary artery aneurysms, a giant Valsalva sinus aneurysm, and ascending aorta dilation. Her parents agreed to a therapy with intravenous immunoglobulin, methylprednisolone, antiplatelet, and anticoagulant, but not to the standard therapy of EBV-HLH. However, the cardiovascular complications, including CAAs and thrombosis, Valsalva sinus aneurysm, and aorta lesions, did not resolve. Three weeks later, the patient was finally discharged home asymptomatic. Unfortunately, one month after discharge, the fever recurred the girl. The guardian had refused treatment and took the patient home due to economic difficulties. During our subsequent follow-up visit, the girl subsequently passed away.ConclusionsWe reported the case of a pediatric patient with EBV infection who developed rare and fatal cardiovascular complications (CAAs and thrombosis, Valsalva sinus aneurysm, and aortic lesions) seven years after the onset of the infection. Clinicians should be aware of these complications during the long-term follow-up of patients with EBV infection, especially in patients with CAEBV and/or EBV-HLH.